A Retrospective Study of Clinico-Etiological Profile of Focal Seizures in Children - Mokase, Yogesh Gangaram; Vaswani, R K; Suryavanshi, Amol Ramrao; Gupta, Swati; Jamdade, Shrikant (Journal of Neonatal Surgery, 2025)
Background: Focal seizures are a common subtype of epilepsy in children, particularly in developing countries where infections are endemic. Understanding their clinical presentation and etiology is essential for effective diagnosis and treatment. Objectives: To evaluate the clinical features and etiological spectrum of focal seizures in children aged 1–12 years at a tertiary care center. Methods: This retrospective observational study included 45 children with focal or focal to bilateral seizures who presented between January 2018 and December 2019. Demographic data, seizure semiology, EEG, neuroimaging, and etiological factors were analyzed using SPSS software. Results: The mean age at presentation was 6.88 ± 3.40 years, with a slight female predominance (57.78%). Focal seizures with impaired awareness (62.22%) and motor onset (80%) were most common. EEG was abnormal in 66.3% of cases, while neuroimaging revealed abnormalities in 68.89%, predominantly ringenhancing lesions (44.45%). Infective granulomas, including neurocysticercosis and tuberculomas, accounted for 44.44% of cases. Structural, metabolic, genetic, and idiopathic causes contributed to the rest. Conclusion: Focal seizures in children are most frequently associated with infectious etiologies, especially neurocysticercosis. EEG and neuroimaging are invaluable in diagnosis and etiological classification. Early detection and targeted therapy are vital in reducing morbidity and preventing chronic epilepsy